Effect of Methods of Nutritional Administration on the Development of Silkworm Bombyx mori L.: Nitrogen Effect on Silkworm Development - Raja, Shazia; Mahmood, Rashid; Sarwar, Ghulam; Iftikhar, Farida; Asad, Saima (Biological Sciences - PJSIR, 2011)
The effect of nitrogen in different concentrations (0.1, 0.2, 0.3 and 0.4 %) through soil, foliar application and dipping of mulberry leaves on food consumption, larval development and cocoon weight of silkworm (Bombyx mori L.) was studied. Larvae when fed on wet mulberry (Morus alba laevigata) leaves dipped in 0.2% N concentration proved the best, as it consumed maximum food (5726.26 mg), gained significantly more weight (3182.30 mg) and produced heavier cocoons (424.65 mg) as compared to all other treatments. Food efficiency ratio (FER: 4.43) and coefficient of utilization (CU: 67.61) were also maximum for the leaves dipped in 0.2% N.